Realization of a closed 1-form on closed oriented surfaces - Budnyts'ka, N. V.; Rybalkina, T. V. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We study closed 1-forms with isolated zeros on closed orientable surfaces. Conditions under which given invariants generate a closed 1-form are found.